NEGATIVE POISSON’S RATIO AND PERCOLATING STRUCTURES - KRZYSZTOF W. WOJCIECHOWSKI (TASK Quarterly, 2001)
Elastic properties of non-uniform, two-component systems are studied in frames of a model of percolation on a simple cubic lattice. It is shown that as the ratio of the bulk moduli of the components tends to zero, ϰ = Ks/Kh → 0 (where s, h denote the softer and harder phase, respectively), the Poisson’s ratio of the system tends to 0.2 at the percolation threshold of the harder phase, no matter what the values are of the Poisson’s ratios of the components. A qualitatively new, collective mechanism leading to negative Poisson’s ratio is suggested.